The genetic diversity, replication, and transmission of 2009 pandemic H1N1 viruses in China - Sun, Hailiang; Wang, Yongcui; Liu, Hanlin; Pang, Zifeng; Cui, Xinxin; Zhao, Rui; Liu, Yanwei; Qu, Xiaoyun; Huang, Mian; Ke, Changwen; Liao, Ming (Frontiers in Microbiology, 2023)
The 2009 pandemic H1N1 influenza A virus (pdm09) continue to evolve, few studies have systemically analysed the evolution, replication and transmission of pmd09 viruses in China. To better understand the evolution and pathogenicity of pdm09 viruses, we systematically analysed viruses that were confirmed in 2009‒2020 in China and characterized their replication and transmission ability. We extensively analyzed the evolution characteristics of pdm/09 in China over past decades. The replication ability of 6B.1 and 6B.2 lineages on MDCK and A549 cells and their pathogenicity and transmission in guinea pigs were also compared. In total, 3038 pdm09 viruses belonged to clade 6B.1 (62% of all pdm09 viruses) and clade 6B.2 (4%). Clade 6B.1 pdm09 viruses are the predominant clade, with proportions of 54.1%, 78.9%, 57.2%, 58.6%, 61.7%, 76.3% and 66.6% in the North, Northeast, East, Central, South, Southwest and Northeast regions in China, respectively. The isolation proportion of clade 6B.1 pdm/09 viruses was 57.1%, 74.3%, 96.1%, 98.2%, 86.7% and 78.5% in 2015‒2020, respectively. A clear differentiation time point appeared in 2015, before which the evolution trend of pdm09 viruses in China was similar to that in North America but then showed a different trend after that point. To characterize pdm09 viruses in China after 2015, we further analysed 33 pdm09 viruses isolated in Guangdong in 2016‒2017, among which A/Guangdong/33/2016 and A/Guangdong/184/2016 (184/2016) belonged to clade 6B.2, and the other 31 strains belonged to clade 6B.1. A/Guangdong/887/2017 (887/2017) and A/Guangdong/752/2017 (752/2017) (clade 6B.1) and 184/2016 (clade 6B.2) replicated efficiently in Madin-Darby canine kidney (MDCK) cells and human lung adenocarcinoma epithelial (A549) cells, as well as the turbinates of guinea pigs. 184/2016 could transmit among guinea pigs through physical contact. Our findings provide novel insights into the evolution, pathogenicity, and transmission of pdm09 virus. The results show that enhancing surveillance of pdm09 viruses and timely evaluation of their virulence are essential.